Strategi Perlindungan Hukum Bagi Nelayan Dalam Menjamin Keberlanjutan Usaha Perikanan Tangkap - Yasser Arafat; Amin, Fakhry (Diktum: Jurnal Ilmu Hukum, 2023)
Indonesia's abundant potential wealth of fishery resources should be a paradise for fishermen. However, it turns out that the condition that occurs is that many fishermen are actually below the poverty line. In Tarakan, a number of fishermen switched professions to become seaweed cultivators because they thought they could earn higher incomes. This shows that there is a problem with the sustainability of the capture fisheries business. Therefore the government needs to provide protection for fishermen to ensure the sustainability of the capture fisheries business. The purpose of this research is to examine the fishermen's protection strategy that needs to be carried out on the problems faced by fishermen based on the applicable laws and regulations. The research method uses normative legal research by examining the sources of primary and secondary legal materials with analytical techniques using the syllogism method and interpretation methods using deductive thinking patterns. The results of this study indicate that the Central and Regional Governments need to develop a strategic plan for the protection of fishermen which includes the provision of infrastructure and facilities for fishing business, business certainty guarantees, fishing risk guarantees, elimination of high economic cost practices, control of imports of fishery commodities, guarantees of security and safety, and facilitation and legal assistance. At the regional level, strategic plans for protecting fishermen need to be contained in regional regulations.